CИНТЕЗ І ДОСЛІДЖЕННЯ В СЕРЕДОВИЩІ ЕМУЛЯТОРА QCE - Deibuk, V. G.; Gorskyi, G. P. (Vinnytsia National Technical University, 2013)
The aim of present paper is emulation and exploration of primitive quantum logical elements by QCE emulator tools. This emulator is based on Izing quantum computer hardware model.